Global burden of anemia attributed to chronic kidney disease: prevalence, years lived with disability, and predictions to 2035 (Global burden of disease 2021) - Zheng, Wenshuai; Chen, Huaxin; Zhang, Wentao; Cai, Yibo; Wu, Zongze; Guan, Lixun (Frontiers in Nutrition, 2025)
BackgroundAs a common complication of chronic kidney disease (CKD), anemia is associated with increased mortality and reduced quality of life. Despite its severe impact, there is a lack of high-quality data on the global burden of anemia attributed to CKD. This study aims to provide a comprehensive analysis of the anemia burden attributed to CKD.MethodsUsing data from the Global Burden of Disease study (GBD) 2021, we report the prevalence and years lived with disability (YLDs) of anemia attributed to CKD across different sexes, ages, and regions; assess the association between anemia burden attributed to CKD and the socio-demographic index (SDI); and quantify and predict temporal trends of anemia burden attributed to CKD.ResultsIn 2021, there were 63.75 million (95% uncertainty interval [UI]: 59.05 to 68.37) cases and 1.70 million (95% UI: 1.13 to 2.43) YLDs of anemia attributed to CKD globally. Compared with 1990, the prevalence and YLDs increased by 96.24 and 74.78%, respectively, which was largely driven by population growth and aging. The global age-standardized prevalence rate (ASPR) and YLD rate per 100,000 were 762.12 (95% UI: 707.32 to 817.37) and 20.34 (95% UI: 13.54 to 29.09) in 2021, which decreased by 9.39 and 18.93% in comparison with those in 1990. However, the decline in ASPR stagnated after 2010, with a slight increase observed between 2010 and 2015. A negative relationship between SDI and the anemia burden attributed to CKD was observed at both regional and national levels. Women had higher ASPR and age-standardized YLD rates compared to men, and the burden attributed to CKD increased with age. Predictive analysis indicated that the prevalence of cases will continue to rise, while the YLDs, ASPR, and age-standardized YLD rates are expected to decline consistently.ConclusionAnemia attributed to CKD is a major public health issue across the world, with persistent regional and socioeconomic disparities. Continued efforts, including addressing socioeconomic disparities, improving access to healthcare, and innovative treatments, are essential to reduce the anemia burden attributed to CKD.